Application of Nonsurgical Modalities in Improving Facial Aging - Kelun Li; Fanyu Meng; Yu Ru Li; Yueyi Tian; Hao Chen; Qi Jia; HongXin Cai; Heng Bo Jiang (International Journal of Dentistry)
Objective. This review aims to summarize different kinds of applications of minimally invasive surgery in improving facial aging to provide a comprehensive and accurate introduction on the issue of esthetic treatment of facial skin. Overview. In the twentieth century, facial rejuvenation has become a new beauty trend. Facial cosmetology has entered a period of antiaging and rejuvenation therapies and microplastic surgery. The pursuit of beauty has promoted the development of minimally invasive plastic surgery. This review introduces the possible causes of facial aging and its related topics with a focus on facial injectable drugs, such as botulinum toxin, main filler materials (hyaluronic acid, calcium hydroxyapatite, poly L-lactic acid, collagen, autologous fat, and polymethyl methacrylate), and some current antiwrinkle technologies, such as thread lift and radiofrequency rhytidectomy. Conclusions. Despite the difference in mechanisms of action, each technique can address facial aging involving the loss of collagen, displacement and enlargement of fat, and muscle relaxation. Combinations of these treatments can provide patients with reasonable, comprehensive, and personalized treatment plans.